2011
DOI: 10.5578/tt.2385
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in NRAMP1 and MBL2 genes and their relations with tuberculosis in Turkish children

Abstract: ÖZET Çocukluk çağı tüberkülozunda genetik yatkınlık

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Several studies have found a significant association between the frequency of structural alleles or promoter polymorphisms and serum MBL levels with susceptibility to TB [20, 23, 24, 2630] while others did not find any significant association [19, 21, 25]. Recently a meta-analysis of 17 human trials considering the effect of MBL2 genotype and/or MBL levels and TB infection did not found significant association between MBL2 genotype and pulmonary TB infection [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a significant association between the frequency of structural alleles or promoter polymorphisms and serum MBL levels with susceptibility to TB [20, 23, 24, 2630] while others did not find any significant association [19, 21, 25]. Recently a meta-analysis of 17 human trials considering the effect of MBL2 genotype and/or MBL levels and TB infection did not found significant association between MBL2 genotype and pulmonary TB infection [22].…”
Section: Introductionmentioning
confidence: 99%
“…Potential malfunction of these aspects may affect innate and adaptive immune responses to M. Tuberculosis infection (6). In some studies performed in different ethnical population, weak and/or strong evidence of linkage was found between Nramp1 and TB (10)(11)(12)(13)(14)(15)(16)(17)(18). Polymorphisms in the Nramp1 gene have also been found in a number of genetic studies to be risk factors for the development of TB among adult populations (13)(14)(15)18).…”
mentioning
confidence: 99%
“…The authors hypothesized that heterozygosity for MBL2 variant alleles, responsible for low serum MBL levels, was associated with protection against clinical TB. Studies in Danish patients [13] and Turkish children [42] showed no association between MBL2 polymorphisms at the codons 54 and susceptibility to TB. A large study in India showed that a significantly increased genotype frequency of MBL mutant homozygotes was seen in pulmonary TB patients as compared with that in control subjects [59].…”
Section: Discussionmentioning
confidence: 91%
“…PCR amplification products were analyzed on a polyacrylamide gel to detect alterations in PCR-amplified products. The primer sequences were previously reported [27,39,42] and listed in Table 1. To ensure the validity of result, we also did the DNA sequencing on the 5% representative isolates to check the PCR.…”
Section: Genotypingmentioning
confidence: 99%